The “Night Battle” of Singara: Whose Victory? - DMITRIEV, Vladimir (Historia i Świat, 2015)
The so-called “Night Battle” of Singara (344 AD) still remains poorly studied historical event because of discrepancies between the sources. The outcome of the battle is described in them with considerable discrepancies too. The analysis of the sources from the point of view of the “classical theory of war” elaborated by C. Clausewitz, unambiguously demonstrates that the winning side in this battle were Persians.